Sensor-Based Assistive Technology as a Support to Reduce Intra-hospital Infection and Mortality Due to Epidemic Respiratory Diseases: A Proposal - Lizarazo-Gutiérrez, Javier; Ortiz-Barrios, Miguel; de Souza, Helder Celani [UNESP]; Jiménez-Delgado, Genett Isabel; Ariza-Ortiz, Andrés; Fernández-Mendoza, Zaury Estela; Alfaro-Parada, Natali Johanna (Springer Nature, 2024)
The rapid spread of Seasonal Respiratory Diseases (SRDs) has put hospitals in need of improving their preventive measures. Contact and proximity are two events that cause the transmission of most respiratory infections. For this reason, the infected patients are generally placed in isolation. Still, even so, they must receive care in hospitals where contact and proximity are almost inevitable i) between patients, ii) between health professionals and patients, and iii) between health professionals, causing intra-hospital transmission of SRDs. This paper presents the design of a sensor-based Assistive Technology (AT) as a support to reduce intra-hospital infection and mortality due to epidemic respiratory diseases. Initially, we characterized the main SRDs. Second, we defined the leading clinical indicators to be monitored in patients with an SRD. Then, we designed the healthcare protocols responding to health deviations in patients with SRD. Fourth, we characterized the targeted population in terms of sociodemographic indicators that may affect the operationalization of the AT in the wild. Finally, we laid the groundwork for the sensor-based AT design. This proposal is an effort to ensure the continuing care of patients with SRD, reducing overcrowding and waiting times in healthcare systems during these periods and consequently tackling high mortality rates.
Keywords: Assistive Technologies (ATs); Healthcare; Intra-hospital Infection; Seasonal Respiratory Diseases (SRDs); Sensor-based Systems